2021
DOI: 10.1094/phyto-11-20-0526-r
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas savastanoi pv. mandevillae pv. nov., a Clonal Pathogen Causing an Emerging, Devastating Disease of the Ornamental Plant Mandevilla spp.

Abstract: Commercial production of the ornamental plant dipladenia (Mandevilla spp.) is threatened by dipladenia leaf and stem spot disease, caused by the bacterium Pseudomonas savastanoi. P. savastanoi includes four pathovars of woody hosts differentiated by a characteristic host range in olive, oleander, ash and broom plants. However, isolates from dipladenia have not been ascribed to any particular lineage or P. savastanoi pathovar. Here we report that isolates from dipladenia represent a distinct, clonal lineage. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…During the last decade, it has been reported that bacterial species of the P. syringae complex can naturally lack the hrp / hrc cluster, making them unable to induce HR in non-host plants or compromising their ability to cause disease in their respective hosts [ 19 , 20 , 21 ]. Genomic analysis carried out for Psv NCPPB 3335, Psn Psn23 , Psm Ph3, Psf NCPPB 1006, and Psr CECT 4861 confirmed that all of these strains contain a canonical hrp / hrc cluster [ 39 , 44 ], which allows them to cause disease symptoms in their respective woody hosts ( Figure 2 ). In the P. syringae complex, the role of HrpL as a global regulator of virulence has been mainly studied in pathogenic bacteria affecting herbaceous plants [ 48 , 49 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…During the last decade, it has been reported that bacterial species of the P. syringae complex can naturally lack the hrp / hrc cluster, making them unable to induce HR in non-host plants or compromising their ability to cause disease in their respective hosts [ 19 , 20 , 21 ]. Genomic analysis carried out for Psv NCPPB 3335, Psn Psn23 , Psm Ph3, Psf NCPPB 1006, and Psr CECT 4861 confirmed that all of these strains contain a canonical hrp / hrc cluster [ 39 , 44 ], which allows them to cause disease symptoms in their respective woody hosts ( Figure 2 ). In the P. syringae complex, the role of HrpL as a global regulator of virulence has been mainly studied in pathogenic bacteria affecting herbaceous plants [ 48 , 49 , 79 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that the repertoire of bacterial T3Es, as well as the repertoire of plant resistance genes, can vary among bacterial strains or cultivars, thus conditioning the induction of a characteristic HR [ 76 , 77 ]. Furthermore, the characterization of strains Psn Psn23 and Psm Ph3 shows that they contain a truncated version of avrPto1 , which encodes a shorter version of the effector with a C-terminal deletion [ 39 , 44 ]. In this sense, it has been described that point mutations occurring at the C-terminal of AvrPto1 prevent HR formation in tobacco but not in tomato leaves, indicating that this part of the effector could participate in its recognition by the plant resistance protein [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations